Living with an Archaic Treaty: Solving the Problem of the Warsaw Convention’s Gold Clause - Hastings, W K (Victoria University of Wellington Law Review, 1996)
Article 22 of the Warsaw Convention for the Unification of Certain Rules Relating to International Carriage By Air limits carriers’ liability by reference to the franc Poincaré or gold franc, a standard that no longer exists. Until the Montreal Protocols come into force or a revised and consolidated Convention is created, the author proposes a method that relies on cooperation between the executive and the courts to keep Article 22 alive and useful.